Enzymatic activity and virulence of Cordyceps locustiphila (Hypocreales: Cordycipitaceae) on the South American locust Schistocerca cancellata (Orthoptera: Acrididae) - Pelizza, Sebastián Alberto (2021)
The first barrier, when penetrating an insect host, encountered by microorganisms like fungi is insects cuticle; fungi produce a wide variety of extracellular enzymes involved in the degradation of protein, chitin, and lipids. The main objectives were to assay the enzymatic activity of Cordyceps locustiphila anamorph, in solid and liquid medium at different temperatures and also to evaluate the pathogenicity against the South American locust, Schistocerca cancellata. Conidia of C. locustiphila anamorph were adjusted to 1 × 104, 1 × 106 and 1 × 108 conidia/ml and mortality was recorded for S. cancellata nymphs. The enzymatic activities were determined through a plate test and liquid medium. When assessing the pathogenicity, the fungus caused the highest mortality (84.5 ± 3.5%) at a dose of 1 × 108 conidia/ml. The proteolytic activity showed the highest values (1.56 ± 0.21) (U) at 26 °C. The highest lipolytic activity (1.13 ± 0.36) (U) was observed at 26 °C, while the highest chitinolytic activity was of 0.85 ± 0.1 (U) at 4 °C. Significant differences were observed for enzymatic production on liquid medium, the highest values were recorded for chitinolytic activity (1.63 ± 0.04) (U) and the lowest for caseinolytic activity (0.04 ± 0.001) (U). The results obtained on mortality as well as the quality and variety of enzymes produced by C. locustiphila suggest that this fungus has features that make it a good candidate to be used as a biological agent for the control of the South American locust.